A school meals program implemented at scale in Ghana increases height-for-age during midchildhood in girls and in children from poor households: A cluster randomized trial - Gelli, Aulo; Aurino, Elisabetta; Folson, Gloria; Arhinful, Daniel K.; Adamba, Clement; Osei-Akoto, Isaac; Alderman, Harold (Elsevier, 2019)
Attention to nutrition during all phases of child and adolescent development is necessary to ensure healthy physical growth and to protect investments made earlier in life. Leveraging school meals programs as platforms to scale-up nutrition interventions is relevant as programs function in nearly every country in the world.